Blockchain's role in promoting quality, safety and sustainability in the food and beverage industry - Nir Kshetri (International Telecommunications Society (ITS), 2023)
The purpose of this paper is to examine the potential roles of blockchain in ensuring quality, and safety and promoting sustainability in the production and distribution of food and beverage products. A multiple case study approach has been chosen as the principal methodology. The article highlights how blockchain deployment in inter-organizational transactions reduces uncertainty in the actions of supply chains participants and makes dependence among value chain partners more symmetric, which can help improve quality and safety and promote sustainability in the food and beverage industry. It describes how blockchain's impact on interfirm governance structures in the food and beverage industry can be improved by increasing the number and types of participants. Also discussed is how blockchain's impact on reducing interfirm governance structures in the food and beverage industry can be improved by combining this technology with other emerging technologies. Finally, it considers how blockchain-based solutions can increase the degree of distributive fairness in the food and beverage industry and improve small-holder farmers' chance of being integrated in the global economy. The article gives special consideration to blockchain's potential in improving interfirm governance in the food and beverage industry. It explains how blockchain may reduce uncertainty in the actions of supply chain participants. The article shows how blockchain can make dependence among supply chain partners more symmetric. It suggests that by stimulating entrepreneurial opportunities for marginalized groups and promoting distributive fairness, blockchain can help take actions that are socially responsible.
Keywords: 330; blockchain; food and beverage industry; interfirm relationships; smart contracts; sustainability; uncertainty